Exploration of polymer-based nanocomposites as dopamine electrochemical sensors / Chang Yeet Hoong - Chang , Yeet Hoong (2022)
The present thesis aims to explore novel polymer-based nanocomposites for electrochemical sensing of dopamine (DA), where the right balance of this neurotransmitter is vital for both physical and mental wellbeing. In the first part of the work, poly-beta-cyclodextrin (poly-β-CD) integrated with oxidized multi-walled carbon nanotubes (poly-β-CD(f-MWCNT)) was synthesized via one-pot electropolymerization method. The anion-doped polyaniline (PANI) was as the substrate due to its high surface area characteristic has successfully overcome the issue of ineffective loading of poly-β- CD(f-MWCNT). The result demonstrated that poly-β-CD(f-MWCNT)/PANI nanocomposites had accomplished the separation of DA signal from the disturbance of interferences’ signals e.g. ascorbic acid (AA) and uric acid (UA); besides manifested a good sensing behavior with high sensitivity of 26.79 μA μM−1 cm−2. The second part of this work aim to replace the conventional ungreen acidic electrolyte in synthesizing polymelamine (PME) with Type III deep eutectic solvents (DES). Three different Type III DES scilicet ethaline, glyceline, and reline were studies as the polymerization solvent. A contrastive research was conducted on the synthesis of novel PME in DES with conventional acidic electrolyte and neutral electrolyte. The DES functionalized polymers were compared in the respect of morphology, electrocatalytic behavior, electrochemical sensitivity, and polymer film stability. The principal factors affecting the polymerization of melamine includes the potential range, loading amount of melamine, pH, and temperature of the electrolyte have been further investigated to identify the best PME(DES). The selected PME(ethaline) was then incorporated with f-MWCNT, forming PME(ethaline)/f-MWCNT nanocomposite. The results indicated this nanocomposite offer excellent electrocatalytic activity in DA oxidation with a low detection limit recorded at 0.288 μM (S/N = 3). In addition, both the novel nanocomposites were applied for DA detection in human urine from health volunteers which concluded that the poly-β-CD(f-MWCNT)/PANI and PME(ethaline)/f-MWCNT nanocomposites as the potential materials for DA electrochemical sensing.